Pengaruh Pajak Daerah, Retribusi Daerah, dan Lain-Lain PAD yang Sah Terhadap Kinerja Keuangan Daerah - Wiguna, Komang Aryagus; Jati, I Ketut (E-Jurnal Akuntansi, 2019)
The purpose of this study is to determine the effect of local taxes, regional levies, and other legitimate local revenue on regional financial performance in the Bali Provincial Government. This study uses a quantitative approach with multiple linear regression analysis techniques. The data in this study are secondary data regarding the PAD of Bali Province in the period 2012-2016. The results showed that partially, both local taxes, regional levies, as well as other legitimate local revenues did not have a significant effect on regional financial performance in the Bali Provincial Government. It can be suggested for future researchers to observe other factors that can affect local taxes, regional levies and other legitimate income. Some of the factors mentioned are population, GDP, government expenditure and inflation. Keywords : Regional Tax, Regional Retribution, PAD, financial performance.